The Effect of Teaching-Based Competencies on The Seventh Graders’ Achievement and Their attitudes towards Learning Mathematics in Nablus Governorate - Fares, Saja Akram (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed at identifying the effect of teaching seventh graders a unit of ’’propapility’’ by using Teaching-Based Competencies on their Achievement and attitudes towards learning mathematics. the researcher used the experimental methodology, Further, it was applied on a population from male students of the seventh grade which were applied in 2017-2018 in Palestine. Besides two groups were chosen in one schools which has two seventh grade sections, the first group was the experimental which was taught by using teaching-Based Competencies, and the other was taught using the ordinary method which called the control group . The researcher used two tools in her study, they were, The post-test that measures the achievement of the students, Attitudesscale to measure the student’s attitudes towards learning mathematics. The researcher recommended toAdopt the method of teaching-based competencies in schools without being qualified only in the subject of math, but in other subjects also. And training teachers in the modern teaching methodsThrough the holding of intensive training courses. And provid the environment, possibilities, activities and the effective teacher who improve the use of the surrounding tools in achieving the learning competencies of the students, also adoption of teaching competencies for all stages of education, from kindergarten to university.And to conduct research in the field of teaching competencies and support scientific research on different teaching strategies.